Weryfikacja ważności wyników wyborów na przykładzie sprawy Bush v. Gore - Radajewski, Mateusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The paper discusses the problem of verification of the validity of election results and consideration of the real will of voters in the election process. The starting point for this consideration may be the example of the Bush v. Gore case, in which the federal Supreme Court of the United States decided to what extent the real will of voters, expressed in a different way than the law stipulates, should be considered during the calculation of election results. The author analyses this case and discusses both its real circumstances and the legal arguments the members of the adjudicating panel referred to. To present all the controversy connected with this case, dissenting submitted for the said decision were also analysed thoroughly. After reflecting on the Bush v. Gore case, the author attempts to answer the question whether a similar case could be adjudicated in the same way under the Polish law. For this purpose the problem of equality of voting rights and consideration of the actual intention of voters during elections are discussed with reference to the Polish Constitution and the Election Code. The author refers to the decisions of the Supreme Court in these considerations and comes to the conclusion that also in light of the Polish law only these votes may be counted which were cast in accordance with the rules set by the legislators.
Keywords: equality; electors; validity of election; ballot paper; voter’s will; Elections